Pengaruh Latihan Triangle Run Terhadap Daya Tahan Pada Anggota Ekstrakurikuler Sepakbola SMAN 1 Pebayuran - Royan Ramadhan, Royan; Abidin, Dindin (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2024)
This research aims to analyze the effect of Triangle Run training on the endurance of football extracurricular members at SMAN 1 Pebayuran. The method used was an experiment with a pre-test and post-test design in one group. The sample for this study consisted of 11 students who were active members of the football extracurricular. The instrument used to measure endurance is the Bleep Test. The research results showed a significant increase in students' endurance after undergoing Triangle Run training for one month. The average increase in students' endurance capacity is shown through test results which show positive changes in VO2max values. Hypothesis testing using the t-test method produces a calculated t-value of 13.5, which is greater than the t-table of 1.812, so it can be concluded that Triangle Run training has a significant impact on increasing endurance. This research makes an important contribution to the development of physical training methods, especially in increasing the physical endurance of football players at school level. These results can be a reference for trainers and related agencies to implement Triangle Run training as part of their routine training program.